Integrated membranes system for water application in microbiology/molecular biology - Heba Abdallah; Dina Nadeem Abd-Elshafy; Marwa Shalaby; Kareem Awad; Rola Nadeem; Ahmed Shaban; Mahmoud Mohamed Bahgat (Applied Water Science)
Abstract An integrated membrane filtration system was developed to make water purity suitable for microbiology/molecular biology research. Water samples were collected from outlets in different buildings of the National Research Center and analyzed for their composition before filtration. An integrated membrane system was developed based on mathematical modeling. Flat sheet membranes were produced, including microfiltration, ultrafiltration, and nanofiltration membranes. The flat sheet membranes were converted to a spiral wound module filter to simulate the local market filters and applied in the integrated membrane system that was designed and installed. The produced water was analyzed and compared to molecular-grade water used in different molecular biology/microbiology applications. Both PCR, agarose gel electrophoresis, bacterial liquid cultures, and viral propagation indicated that treated water using the herein-developed system exhibited comparable performance to the molecular grade water provided with imported reagent kits. So, this research can offer a promising solution for producing high-quality water suitable for sensitive laboratory applications.